Using of the Virtual Reality Application with the Scanning Device Kinect for Manufacturing Processes Planning - Novak-Marcincin, Jozef; Fecova, Veronika; Barna, Jozef; Janak, Miroslav; Novakova-Marcincinova, Ludmila (Manufacturing Technology Journal, 2013)
Introduction into problems - This article is focused on the area of virtual reality, in the concrete to the creation of application and its using. The applications are usually used with the expensive display devices and expensive motion tracking devices. For the application of virtual reality technology is currently available the several motion tracking devices, which have different prices. This contribution describes the using of application with the Kinect device, which is affordably priced. Kinect is a device that needn't for control any physical controller, because uses only the user's movements, which are transferred to the application. By using of virtual reality technology is very simply to compare the different versions of a solution and simply eliminate the found mistakes. And if the whole product design is proposed, controlled and simulated by using VR, in the production process should be no bigger problems.
Keywords: virtual reality; Kinect; motion tracking